Acceptability and feasibility of an online information linker service for caregivers who have a child with genetic epilepsy: a mixed-method pilot study protocol. Issue 10 (26th October 2022) - Robertson, Eden G; Kelada, Lauren; Best, Stephanie; Goranitis, I; Grainger, Natalie; Le Marne, Fleur; Pierce, Kristine; Nevin, Suzanne M; Macintosh, Rebecca; Beavis, Erin; Sachdev, Rani; Bye, Annie; et al.
Abstract : Introduction: Developmental and epileptic encephalopathies (DEEs) are rare epilepsy conditions that collectively impact 1 in 2000 children. They are highly genetically heterogeneous, resulting in significant barriers to accurate and adequate information for caregivers. This can lead to increased distress and dissatisfaction with the healthcare system. To address this gap, we developed 'GenE Compass' to provide caregivers with the highest-quality possible, understandable and relevant information in response to specific questions about their child's DEE. Using a mixed-method design, we will now pilot GenE Compass to evaluate the acceptability to caregivers and clinicians, feasibility and impact to caregivers. Methods and analysis: We will recruit 88 caregivers (estimated final sample of 50 at follow-up) who have a child under 18 years of age with a suspected or confirmed DEE diagnosis. Following consent and a baseline questionnaire (questionnaire 1 (Q1)), participants will be able to submit questions to GenE Compass over a 3-month period. After 3 months, participants will complete a follow-up questionnaire (Q2) and an optional telephone interview to answer the research questions. Primary outcomes are acceptability of GenE Compass and feasibility of delivering the intervention (eg, cost of the intervention, number of questions submitted and time taken to respond to questions). Secondary outcomes include the impact of GenE Compass on caregivers' quality of life, information searching behaviours, perceptions of their child's illness and activation. Ethics and discussion: The study protocol (V.2, dated 16 September 2021) has been approved by the Sydney Children's Hospitals Network Human Research Ethics Committee (ETH11277). The results will be disseminated in peer-reviewed journals and at scientific conferences. A lay summary will be disseminated to all participants. Trial registration number: ACTRN12621001544864.